The Relationship between Parental Monitoring of Gadget Use with Social Emotional Development of Children Age 5-6 Years at RW 03 - Putri Miranti; Ismaniar Ismaniar (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
This study is motivated by the low socio-emotional development of children between the ages of 5 and 6 years, which is likely due to the extent of children's dependence on using certain media like gadgets and calls for extra caution to minimize it. the socio-emotional development of children between the ages of 5 and 6 in RW 03 and the relationship between parental supervision of technology use and the socio-emotional development of children between the ages of 5 and 6 in RW 3. This type of research is quantitative and correlative. Parents with children who were between the ages of 5 and 6 years old, as well as up to 56 other people, made up the study's population. 32 people used the stitch probing technique. Daten An evaluation tool called a questionbogen is used, and the percent formula and the product moment are used in data analysis. The findings revealed that while the category's description of older users' oversight of gadget use was favorable, the category's description of younger users' socioemotional growth (children aged 5–6 years) lagged behind. Additionally, there is a correlation between parental supervision of children's device use and their social and emotional development in RW 03 when they are between the ages of 5 and 6, but this correlation is weak because r table = 0,304. According to Sugiyono, the r-Wert belongs to the middle category because it falls within the range of (0,40-0,59), which is equal to 0,454.Keywords: parental supervision, social emotional development, gadget